2013
DOI: 10.1037/a0030766
|View full text |Cite
|
Sign up to set email alerts
|

In the eye of the beholder: Thin-ideal media affects some, but not most, viewers in a meta-analytic review of body dissatisfaction in women and men.

Abstract: The issue of thin-ideal (or muscularity ideal for males) media effects on viewers continues to be debated and discussed within the scientific community. Many scholars have concluded that thin-ideal media can have an appreciable effect on viewers. More recently several scholars have contested this issue suggesting that media effects may be small to negligible or limited to groups of individuals already at risk for body dissatisfaction. The current meta-analysis, the most comprehensive to date with 204 studies, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
125
3
9

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 159 publications
(153 citation statements)
references
References 56 publications
(110 reference statements)
8
125
3
9
Order By: Relevance
“…The findings of this study add to the body of evidence suggesting that individuals are differentially affected by exposure to thin-ideal media (Ferguson 2013). Of most interest are the novel findings relating to media literacy that show contrasting effects for participants with high and low levels of this protective factor.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…The findings of this study add to the body of evidence suggesting that individuals are differentially affected by exposure to thin-ideal media (Ferguson 2013). Of most interest are the novel findings relating to media literacy that show contrasting effects for participants with high and low levels of this protective factor.…”
Section: Discussionmentioning
confidence: 69%
“…Stability, or even improvement in body satisfaction following thin-ideal media exposure, has been observed (Durkin and Paxton 2002;Knobloch-Westerwick and Crane 2012). Authors have argued that effects are weak (Holmstrom 2004) or apparent only for those with existing vulnerability (Ferguson 2013). The aim of this study was to examine factors that predict change or stability in body satisfaction in early adolescent girls following exposure to thin-ideal media.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, several meta-analyses of experimental studies have concluded that acute exposure to lean and muscular images of men leads to increases in body dissatisfaction (Barlett et al, 2008;Blond, 2008;Ferguson, 2013), as well as depressed mood, disordered eating and other related health problems (Hausenblas et al, 2013) for some men. This evidence and research highlights the appearance potency (e.g., via its resultant effects on men's body dissatisfaction) of appearance ideal and sexualized media content.…”
Section: What Elements Of the Media Are Appearance Potent?mentioning
confidence: 99%
“…Future research could usefully employ then Elliott and Elliott's (2005) 'readership-response' method (in which a participant guides the researcher through their responses to media). In addition to employing other qualitative techniques to better understand men's experiences of the media, given that consumption is a reciprocal, complex and highly individualized process (Elliott & Elliott, 2005;Ferguson, 2013;Wykes & Gunter, 2005). …”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%
“…One could actually make the argument from this study that it is better to use sexualized avatars so long as they do not have one's own face. However, both studies in reality have potential flaws such as rather blatant demand characteristics, a problem unfortunately common to media/ body image research (Ferguson 2013a;Want 2014;Whyte et al 2016).…”
Section: On "Sexist" Gamesmentioning
confidence: 99%